2002
DOI: 10.3989/scimar.2002.66s35
|View full text |Cite
|
Sign up to set email alerts
|

Marine benthic algae of Namibia

Abstract: SUMMARY: The first comprehensive study of the marine algal flora of Namibia including descriptions and illustrations of most species is presented. The main objective of this work is to report a flora that, until now, has scarcely been studied. The work compiles all the available information on the marine benthic flora of Namibia and provides new data about it composition and biogeography, as well as detailed descriptions and remarks of most of its species. The samples on which this study is based were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 164 publications
1
7
0
1
Order By: Relevance
“…The distant relationships of P. arenosa and P. pennata from the putative relatives raise questions about divergence pathways, which will be reinvestigated through additional taxon sampling within the genus. Moreover our results also clarify the distinction between P. cloiophylla from South Africa and P. complanata from Europe (2.2% of sequence divergence), for which the synonymy have been previously suggested (Rull Lluch 2002). Differences between Pterosiphonia and Symphyocladia have been said to be slight and insubstantial (Kraft and Wynne 1992).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The distant relationships of P. arenosa and P. pennata from the putative relatives raise questions about divergence pathways, which will be reinvestigated through additional taxon sampling within the genus. Moreover our results also clarify the distinction between P. cloiophylla from South Africa and P. complanata from Europe (2.2% of sequence divergence), for which the synonymy have been previously suggested (Rull Lluch 2002). Differences between Pterosiphonia and Symphyocladia have been said to be slight and insubstantial (Kraft and Wynne 1992).…”
Section: Discussionsupporting
confidence: 56%
“…Molecular techniques also allow us to answer questions on determining the species without clear-cut morphological diagnostic criteria. This is the case of the genus Pterosiphonia where several synonymies have been suggested due to the species are distinguished solely based on a few vegetative characters, which overlapping in some species (Rull Lluch 2002, Díaz Tapia and Bárbara 2004, 2011, Gabrielson et al 2004.…”
Section: Molecular Studymentioning
confidence: 99%
“…Another collection similar to both H. arbuscula and C. hypneoides was described from Namibia as 'Hypnea sp.' (Rull Lluch, 2002). We have examined these Namibian specimens (BCF-A 1167) and observed that, in addition to the morphological features described by Rull Lluch (2002), they also have refractive inclusions in the outer cortical cells, as in C. hypneoides.…”
Section: Discussionmentioning
confidence: 89%
“…are large-celled, attached filaments, the distal cells becoming almost spherical and up to about 2 mm in diameter (Simons 1976) and basal cells 5-12 mm long. This species is restricted to South Africa (Stegenga et al 1997) and Namibia (Rull Lluch 2002). Chaetomorpha moniligera Kjellm., with a distribution restricted to Japan and Korea, is also a species with attached, large-celled filaments.…”
Section: Methodsmentioning
confidence: 99%